METODOLOGI ILMU PENGETAHUAN BUDAYA / KEMANUSIAAN - Agus Salim; Ridha Ahida; Yusri Yaldi (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2024)
The aim of this research is to determine the methodology of cultural/humanitarian sciences. This paper was written using the library research method, namely a study of several literature or scientific works related to the methodology of cultural/human sciences. The results of the research show that: 1) Science is an actualization that originates from knowledge derived from reason and regulations, 2) Culture Research into the culture of a society, whether regarding its cultural products, or cultural behavior, or the ideas behind its behavior or products, tends to show mixed results, 3) Research can use various methods and approaches, ranging from field research to textual analysis.